M MENELADANI AKHLAK SITI FATIMAH AZ-ZAHRA: INSPIRASI PENDIDIKAN KARAKTER ISLAMI DARI KARYA AL-HAMID AL-HUSAINI - Zainuddin, Zainuddin; Mufidah, Ana (JURNAL PUSAKA: Media Kajian dan Pemikiran Islam, 2025)
This article examines the moral education values reflected in the life of Siti Fatimah Az-Zahra, the daughter of the Prophet Muhammad (peace be upon him), based on the historical study from the perspective of H. M. H. Al-Hamid Al-Husaini. Employing a qualitative approach and content analysis method on the works of Al-Hamid Al-Husaini, this research highlights the personality and role of Siti Fatimah as a daughter, wife, mother, and exemplar of noble character within the Islamic family context. The findings indicate that Siti Fatimah Az-Zahra represents an ideal Muslim woman, embodying piety, sincerity, humility, and total devotion to Allah SWT, the Prophet, and her family. These values serve as an essential foundation for moral education and the cultivation of noble character within families and society. This study also explores how Al-Hamid Al-Husaini constructs a historical narrative rich in praise for the Ahlul Bait, while emphasizing the significance of Siti Fatimah’s exemplary conduct in building an ethical Islamic civilization. Key words: Siti Fatimah Az-Zahra, Character Education and Historical Studies.